Treatment discontinuation following low-dose TKIs in 248 chronic myeloid leukemia patients: Updated results from a campus CML real-life study - Iurlo, A.; Cattaneo, D.; Consonni, D.; Castagnetti, F.; Miggiano, M. C.; Binotto, G.; Bonifacio, M.; Rege-Cambrin, G.; Tiribelli, M.; Lunghi, F.; Gozzini, A.; Pregno, P.; et al. (Frontiers in Pharmacology, 2023)
TKIs long-term treatment in CML may lead to persistent adverse events (AEs) that can promote relevant morbidity and mortality. Consequently, TKIs dose reduction is often used to prevent AEs. However, data on its impact on successful treatment-free remission (TFR) are quite scarce. We conducted a retrospective study on the outcome of CML subjects who discontinued low-dose TKIs from 54 Italian hematology centers participating in the Campus CML network. Overall, 1.785 of 5.108 (35.0%) regularly followed CML patients were treated with low-dose TKIs, more frequently due to relevant comorbidities or AEs (1.288, 72.2%). TFR was attempted in 248 (13.9%) subjects, all but three while in deep molecular response (DMR). After a median follow-up of 24.9 months, 172 (69.4%) patients were still in TFR. TFR outcome was not influenced by gender, Sokal/ELTS risk scores, prior interferon, number and last type of TKI used prior to treatment cessation, DMR degree, reason for dose reduction or median TKIs duration. Conversely, TFR probability was significantly better in the absence of resistance to any prior TKI. In addition, patients with a longer DMR duration before TKI discontinuation (i.e., >6.8 years) and those with an e14a2 BCR::ABL1 transcript type showed a trend towards prolonged TFR. It should also be emphasized that only 30.6% of our cases suffered from molecular relapse, less than reported during full-dose TKI treatment. The use of low-dose TKIs does not appear to affect the likelihood of achieving a DMR and thus trying a treatment withdrawal, but might even promote the TFR rate.